Hair cell regeneration, repair, and protection - Salvi, Richard J. (Springer, 2017)
Overview: regeneration and repair / Richard J. Salvi -- Morphological correlates of regeneration and repair in the inner ear / Jason R. Meyers and Jeffrey T. Corwin -- Recovery of function in the avian auditory system after ototrauma / James C. Saunders and Richard J. Salvi -- Functional recovery after hair cell regeneration in birds / Robert J. Dooling, Micheal L. Dent, Amanda M. Lauer, and Brenda M. Ryals -- Hair cell regeneration : mechanisms guiding cellular proliferation and differentiation / Elizabeth C. Oesterle and Jennifer S. Stone -- Protection and repair of inner ear sensory cells / Andrew Forge and Thomas R. Van De Water -- Gene arrays, cell lines, stem cells, and sensory regeneration in mammalian ears / Marcelo N. Rivolta and Matthew C. Holley.